Sexual practices, sexual behavior and HIV risk profile of key populations in Nigeria - Bartholomew Ochonye; Morenike Oluwatoyin Folayan; Adesegun O. Fatusi; Bamidele M. Bello; Babatunde Ajidagba; Godwin Emmanuel; Paul Umoh; Ayo Yusuf; T. Jaiyebo (BMC, 2019)
Abstract Background There is little evidence on the need for differentiated HIV prevention services for men who have sex with men (MSM), female sex workers (FSW) and people who inject drugs (PWID in Nigeria. The aim of the study was to determine and compare the HIV sexual risk profiles of FSW, MSM and PWID resident in Nigeria; and identify factors associated with condom use among the groups. This will help identify if differentiated HIV prevention services are needed for MSM, FSW and PWID in Nigeria. Methods This is a cross-sectional study. Data on sexual practices (anal, vaginal and oral sex), history of alcohol and psychoactive substance use, and high risk sexual behaviors for HIV infection (inconsistent use of condom) was collected from study FSW, MSM and PWID resident in Enugu, Nassarawa, Benue, and Akwa-Ibom States of Nigeria between April and June, 2015. Association between sexual practices, alcohol and psychoactive substance use, and HIV sexual risk behaviors; and differences in sexual risk behaviors of MSM, FSW and PWID were determined using Pearson chi-square for categorical variables, and t-test for continuous variables. Determinants of condom use in the last 30 days were identified using logistic regression analysis. Results The study population consisted of 188 (38.5%) FSW, 145 (29.7%) MSM and 155 (31.8%) PWID. MSM (AOR: 0.17; 95%CI: 0.05-0.67; p = 0.01) and PWID (AOR: 0.07; 95%CI: 0.02-0.21; p < 0.001) were significantly less likely than FSW to have used condom in the last 30 days. A lower proportion of FSW and PWID used condom during anal sex in the last 12 months when compared with MSM (p < 0.001 respectively). The proportion of MSM (23.5%) and FSW (23.4%) who had ever used psychoactive drugs was high. Of those who had ever used psychoactive drugs, 25.0% of FSW and 29.4% of MSM had injected drugs in the last 30 days of the survey. Also, 39.3% of PWID shared needles and syringes. The use of psychoactive substances (AOR: 5.01; 95%CI: 2.59-9.68; p < 0.001) and the ability to negotiate condom use (AOR: 2.04; 95%CI: 1.06-3.93; p = 0.03) were factors associated with condom use in the last 30 days of the survey. Conclusion HIV prevention programs designed for MSM, FSW and PWID need to address inconsistent condom use during sex by addressing condom negotation skills. This sexual risk behavior is common to the three groups.